2018
DOI: 10.1007/s10067-018-4124-0
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant T cell subsets and cytokines expression profile in systemic lupus erythematosus

Abstract: To assess T cell subsets and levels of chemokines and cytokines in patients with SLE and determine their relationships between disease activity and organ involvement. Blood samples from SLE patients (n = 24) and healthy controls (n = 36) were analyzed. Frequency of circulating follicular help T cells (Tfh), central memory T cells (Tcm), effector memory T cells (Tem), and naïve T cell subsets was enumerated and their surface markers expression of inducible T cell co-stimulator (ICOS) and programmed death 1(PD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…The expression of checkpoint molecules such as PD-1 and TIGIT have been reported to be dampened on immune cells in SLE patients [22, 23]. However, in our study, SLE subjects seemed to exhibit increased levels of PD-1, similar to what has been just revealed in systemic sclerosis [24] and another study showing that SLE patients exhibited increased frequencies of circulating PD1 + ICOS + T follicular helper cells and PD1 + ICOS + T memory cells [25], possibly suggesting a feedback mechanism of the immune system. These inhibitory receptors could have failed to suppress overwhelming T cell activation as a result of upregulation of other activation pathways.…”
Section: Discussionsupporting
confidence: 77%
“…The expression of checkpoint molecules such as PD-1 and TIGIT have been reported to be dampened on immune cells in SLE patients [22, 23]. However, in our study, SLE subjects seemed to exhibit increased levels of PD-1, similar to what has been just revealed in systemic sclerosis [24] and another study showing that SLE patients exhibited increased frequencies of circulating PD1 + ICOS + T follicular helper cells and PD1 + ICOS + T memory cells [25], possibly suggesting a feedback mechanism of the immune system. These inhibitory receptors could have failed to suppress overwhelming T cell activation as a result of upregulation of other activation pathways.…”
Section: Discussionsupporting
confidence: 77%
“…Consistently, we found that Prevnar-13 was associated with increased IL-10 production by T cells which suppresses the IL-2 production required for T-cell clonal expansion (38, 39). Conversely, production of IL-4 and IL-17, two cytokines associated with active disease (40), were inhibited by Prevnar-13.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence suggesting an augmentation of CD4 + T EM cells population in SLE pathogenesis (44). Also, the PD1 + ICOS + T CM , and PD1 + ICOS + T EM subpopulation are increased in SLE patients and T EM positively cells correlated with the severity of the disease (45). Likewise, it has been observed an enrichment of CD4 + T EM -cell associated genes within SLE loci, Crohn's loci and RA loci (46).…”
Section: Memory T Cells: Key Player In the Pathogenesis Of Autoimmunementioning
confidence: 99%